Comparative Analysis of Scientific Approaches in Computer Science: A Quantitative Study - Kruger, Felix; Queen, Zabenaso; Radelva, Ocean; Lawrence, Neil (Pandawan Sejahtera Indonesia, 2024)
Computer Science is an interdisciplinary field drawing its foundations from a multitude of scientific and engineering domains. The study of Computer Science necessitates the integration of concepts from various fields, blending theoretical frameworks with practical applications. This dual approach, combining abstraction and design, allows for a comprehensive understanding of computational systems. Over the years, the historical evolution of Computer Science has witnessed the emergence of numerous sub-disciplines that increasingly communicate and overlap, driven by the advancement of communication technologies and the growing need for a holistic perspective in understanding complex systems. This interdisciplinary synergy is crucial in addressing contemporary challenges that are inherently multifaceted, requiring inputs from diverse scientific areas. As our world becomes more interconnected and dominated by intricate technological systems, the reductionist approach proves inadequate. Instead, a holistic view, which acknowledges and leverages the interdependencies among various scientific disciplines, becomes imperative. This paper explores the multifaceted nature of Computer Science, highlighting its foundational concepts, historical development, and the integration of theory and practice. It delves into how the convergence of different scientific fields within Computer Science fosters innovation and addresses complex real-world problems. By examining the interdisciplinary interactions and their implications, this study underscores the importance of a comprehensive approach in advancing the field of Computer Science and its applications in solving modern-day challenges.